2003
DOI: 10.1097/00005537-200301000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Radiofrequency‐Induced Thermotherapy of Turbinate Hypertrophy: Pilot Study and 20 Months' Follow‐up

Abstract: The new bipolar radiofrequency thermotherapy presents an efficient option for the treatment of turbinate hypertrophy, which meets the requirements for an outpatient treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 48 publications
(75 reference statements)
2
35
0
4
Order By: Relevance
“…In There are many studies which demonstrated the effectiveness of RFVTR in reducing the nasal obstruction in patients with ITH [1,2,4,[8][9][10][11][12][13] and our finding findings are similar to them.…”
Section: Nasal Obstructionsupporting
confidence: 87%
“…In There are many studies which demonstrated the effectiveness of RFVTR in reducing the nasal obstruction in patients with ITH [1,2,4,[8][9][10][11][12][13] and our finding findings are similar to them.…”
Section: Nasal Obstructionsupporting
confidence: 87%
“…Thus, catastrophic techniques with no respect to nasal functionality, like total turbinectomy, are condemned by many authors [17,22]. Many treatment methods have been reported with various results [17,[23][24][25][26]. Several studies report that treatment of inferior turbinate hypertrophy using bipolar RF offers an efficient alternative to other established methods [27].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to true cautery, which causes damage similar to 3rd degree burns, the tissue damage that does occur with radiofrequency is very superficial and is comparable to that which occurs with lasers [32]. The radiofrequency device allows simultaneous cutting and coagulation of tissues in an atraumatic manner in contrast to the traditional electrosurgical devices.…”
Section: Discussionmentioning
confidence: 99%